Analysis of typical programming mistakes made by first and second year IT students - Kaczorowska, Monika (Journal of Computer Sciences Institute, 2020)
The research paper contains a review and analysis of common programming mistakes made by first and second year students of Computer Science. The data were collected during the courses entitled “Algorithmics and Data Structures” and “Numerical Methods”, where students have to write programs in the C++ language. The article includes examples of three selected mistake types. A comparison of mistakes made by first and second year students is presented. The analysis carried out shows that the percentage of mistakes made decreases when the students are in the second year, but three types of mistakes demonstrate the opposite trend. It can be concluded that those three types of mistakes are related to the course of Numerical Methods, where students have to deal with a significant amount of mathematical expressions. The results show that the students have the most significant problems with memory management.